2021
DOI: 10.1002/adfm.202100633
|View full text |Cite
|
Sign up to set email alerts
|

HtrA3‐Mediated Endothelial Cell–Extracellular Matrix Crosstalk Regulates Tip Cell Specification

Abstract: Angiogenesis is critical in tissue engineering and regenerative medicine. Once initiated, outgrowing capillaries are spearheaded by specialized endothelial cells (ECs) termed tip cells. Specification of tip cells from ECs during angiogenesis is greatly influenced by the surrounding extracellular matrix (ECM). However, the crosstalk between ECs and the ECM in tip cell specification is poorly understood. Here, this study shows that the high-temperature requirement A3 (HtrA3) protein is deeply involved in this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In general, angiogenesis is initiated from a pre-existing vasculature by sprouting ECs . The physiological process of angiogenesis includes a number of stages.…”
Section: Resultsmentioning
confidence: 99%
“…In general, angiogenesis is initiated from a pre-existing vasculature by sprouting ECs . The physiological process of angiogenesis includes a number of stages.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a network-Based analysis showed that PI3K/Akt signaling pathway and Rap1 signaling pathway in human vascular endothelial cells were the two pathways that differentiate into tip cells and stalk cells [ 35 ]. A report displayed that HtrA3 in HUVECs can enhance sprouting, cellular cortical protrusions, and mobility of HUVECs and further promote tip cell formation and tip position competition by activating PI3K/Akt signaling pathway [ 36 ]. In our study, we also found that CRC-CDEs and exosomal circTUBGCP4 can activate Akt signaling pathway to promote tip cell formation in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue processing and sectioning were carried out as previously described 38 . Images were captured using confocal microscopy (Leica).…”
Section: Methodsmentioning
confidence: 99%